The Philippines through the lens of an American soldier, 1898-1907 the Harry Whitfield Harnish photographic collection. - Abaya, Eufracio C.; Alcazaren, Paulo G.; Canta, Marilyn R.; Canete, Reube R.; Datuin, Flaudette May; Duque, Ma. Estella; Flores, Patrick D. (National Commission for Culture and the Arts, 2004)
This collection of photographs and perspectives on aspects of Philippine social life dwells on the vision of an American soldiers as well as on the interdisciplinary outlook of critics of representation and its ramifications. Harry Whitfield Harnish was stationed in the Philippines during the American imperialist occupation of the islands. Returning the look of the dominant gaze of exploration and surveillance unsettles the imagination of conquest as it redeems the possibility of a reciprocal and resistive exchanged of sights in the present.